2021
DOI: 10.1007/s00431-021-04271-0
|View full text |Cite
|
Sign up to set email alerts
|

Lower prevalence of congenital cytomegalovirus infection in Portugal: possible impact of COVID-19 lockdown?

Abstract: Cytomegalovirus (CMV) is the most frequent cause of congenital infection all over the world. Its prevalence ranges from 0.2 to 2.2%. Transmission from children to their pregnant mothers is a well-known risk factor, particularly if they attend a childcare centre. This study aims to compare the prevalence of CMV congenital infection (CMV_CI) in Portugal (Lisbon) between two studies, performed respectively in 2019 and 2020. In the 2019 study, performed in two hospitals, we found a 0.67% CMV_CI prevalence, using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
(23 reference statements)
1
11
2
Order By: Relevance
“…In fact, a dramatic decrease in respiratory syncytial virus infections in the 2020 winter season [5] and a re-emergence of enterovirus D68 after easing the lockdown in 2021 [6] have also been reported, both viruses sharing the contact transmission route with CMV. We agree with Fernandez et al [1] that our findings reinforce the role of behavioral risk reduction interventions to prevent cCMV in pregnant women.…”
supporting
confidence: 93%
“…In fact, a dramatic decrease in respiratory syncytial virus infections in the 2020 winter season [5] and a re-emergence of enterovirus D68 after easing the lockdown in 2021 [6] have also been reported, both viruses sharing the contact transmission route with CMV. We agree with Fernandez et al [1] that our findings reinforce the role of behavioral risk reduction interventions to prevent cCMV in pregnant women.…”
supporting
confidence: 93%
“… 3 , 4 Pregnant women and newborns experienced some limitations in accessibility to health care resources during the pandemic period as well, potentially contributing to a decrease in the diagnosis of congenital infections. 9 Regarding the lack of availability of CMV detection tests, the laboratories of REDICCMV centers did not report a decrease in material resources, so we do not believe that this could be a contributor. Nonetheless, the possibility of a subnotification of new patients to the registry, related to the difficulties in the normal work routines, is low because of the care burden of REDICCMV pediatricians during the pandemic has not increased significantly, so underreporting is not expected.…”
Section: Discussionmentioning
confidence: 91%
“…The results observed may not be generalizable to other countries; however, Fernández et al have already reported a decrease in the prevalence of cCMV comparing 2019 and 2020 in the context of universal screening program carried out in 4 Portuguese hospitals. 9 It would be interesting to maintain continuous surveillance of the prevalence of cCMV to see if this trend continues.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID‐19 pandemic would not have been expected to increase CMV testing or the prevalence of symptomatic cCMV infants. In fact, Fernandez et al noted a reduction in CMV prevalence from 2019 to 2020 possibly due to the COVID‐19 lockdown 20 . Additionally, the number of infants diagnosed with cCMV based on SGA, abnormal head circumference, and other signs and symptoms was greater than those identified based on failed NBHS.…”
Section: Discussionmentioning
confidence: 99%